Dynamic hip system blade versus cannulated compression screw for the treatment of femoral neck fractures: A retrospective study - Chao Chen; Li Yu; Xin Tang; Mo-zhen Liu; Li-zhong Sun; Changjian Liu; Zhen Zhang; Chang-zhou Li (Acta Orthopaedica et Traumatologica Turcica, 2017)
Objective: The aim of this study was to compare clinical outcomes of patients with femoral neck fractures treated with the dynamic hip system blade (DHS-BLADE) or cannulated compression screws. Methods: Eighty-six patients with femoral neck fractures were treated by closed reduction internal fixation with a DHS-BLADE (n = 42; 18 males and 24 females; mean age: 56.3 years (37–87)) or cannulated compression screws (n = 44; 20 males and 24 females; mean age: 53.8 years (26–83)) between March 2011 and August 2013. The groups were compared with Harris hip score, operation time, surgical blood loss, incision size, hospital stay, and related complications. Results: The average follow-up time was 27 months (range, 24–36 months). There was no significant difference for the operation time, incision size, hospital stay, and Harris hip score between the groups. Also, no statistically significant differences in the rates of nonunion (4.5% vs. 0) and avascular necrosis of the femoral head (9.1% vs. 7.1%) were observed. However, the screw group experienced significantly less surgical blood loss (32.4 ± 24.7 ml) than the blade group (87.2 ± 46.6 ml; P = 0.041). The incidence of femoral neck shortening above 10 mm in the screw group was significantly higher than that in the blade group (15.9% vs. 2.4%, P = 0.031). The blade group had a significantly lower incidence of screw migration than the screw group (4.8% vs. 22.7%, P = 0.016). Conclusion: The DHS-BLADE and cannulated compression screws might be equally effective in terms of postoperative fracture union. However, the DHS-BLADE has advantages over cannulated compression screws for preventing femoral neck shortening, screw migration, and cut-out. Level of evidence: Level III, Therapeutic study. Keywords: Femoral neck fracture, Cannulated screw, Dynamic hip system blade, Internal fixation